Carbon fiber surface modification method based on layer-by-layer self-assembly principle
Through the principle of electrostatic layer-by-layer self-assembly, nanoparticles are deposited on the surface of carbon fibers, the problem of functional fillers aggregation in composite materials is solved, uniform distribution and efficient preparation of functional fillers are achieved, and the performance and applicability of composite materials are improved.
Patent Information
- Application Number
- CN202411138869.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
In the preparation process of continuous fiber composite materials, functional fillers aggregate due to the filtration effect of fiber bundles, affecting the mechanical properties and functional characteristics of the material. The existing complex physical and chemical methods increase the preparation cost and are difficult to apply universally.
The carbon fiber surface modification method based on the principle of electrostatic layer self-assembly, and the graphene oxide sheet structure and the opposite charge nanoparticles are assembled on the surface of carbon fiber, and the content of nanoparticles is regulated to achieve uniform distribution of functional fillers. .
The high content distribution of functional fillers on the fiber surface is realized, the filtering effect of fiber bundles on the filler is avoided, the mechanical properties and functional characteristics of the composite material are improved, the preparation cost is reduced, and a simple, efficient and economical method is provided. Construction of structural/functional integrated composite materials.
Smart Images

Figure CN119243480A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of carbon fiber surface modification, in particular to a carbon fiber surface modification method based on the layer-by-layer self-assembly principle. Background technology:
[0002] Carbon fiber reinforced polymer composites are widely used in aerospace, rail transit, new energy and military fields due to their light weight, high specific strength and specific stiffness. With the development of composite materials, in addition to being used as structural load-bearing materials, they can also be used as functional materials to achieve structural / functional integrated design. One of the main ways is to achieve different functional properties by adding functional fillers, such as electrical conductivity, thermal conductivity, electromagnetic shielding and nuclear radiation shielding, especially the use of nanoparticles. Patent CN110343363 adds one or more fillers such as carbon nanotubes, graphene and conductive carbon black to epoxy resin to prepare a conductive carbon fiber composite material. Patent CN114932724 deposits ferroferric oxide nanoparticles and graphene oxide nanoparticles on the surface of carbon fiber cloth by electrohydrodynamic atomization deposition to obtain modified carbon fiber cloth, which is used for the preparation and design of high-strength electromagnetic shielding fiber composite materials. In addition, patent CN113201180 discloses a neutron and gamma ray composite shielding material and its preparation method. The composite shielding material introduces a surface-modified neutron absorber and a gamma ray absorber, so that the material has high-performance neutron absorption ability and a certain gamma attenuation ability. Neutron shielding includes deceleration and absorption. Neutron absorption is usually achieved by containing an absorbing element (B 10 、Cd 113 、Sm 149 )’s functional fillers are introduced, such as B4C, Cd and Sm2O3.
[0003] However, in the preparation process of continuous fiber composite materials, the resin matrix containing functional fillers always accumulates between fiber bundles due to the "filtering effect" of the fiber bundles during the process of impregnating the fibers (Caglar B, Orgéas L, DuRoscoat SR, Sozer EM, Michaud V. Permeability of textile fabrics with spherical inclusions. Composites Part A: Applied Science and Manufacturing. 2017; 99: 1-14.). The aggregation or agglomeration phenomenon caused by the large amount of functional fillers gathered between the bundles will affect the mechanical properties of the final composite material and the performance of its functional characteristics. Therefore, in addition to directly mixing the functional fillers into the resin matrix, the fiber surface can also be modified by more complex physical and chemical methods to achieve the purpose of interface modification and functional design. For example, the fiber is treated with plasma or concentrated acid oxidation to increase the reactive groups on its surface and improve the interfacial bonding strength between the fiber and the resin matrix. Patent CN104195824, in order to solve the problem that existing carbon fibers in near-Earth space orbits are severely eroded by atomic oxygen, resulting in a decrease in carbon fiber performance, is chemically modified to graft bis(3-aminophenyl)phenylphosphine oxide resistant to atomic oxygen onto the surface of carbon fibers, which improves the atomic oxygen corrosion resistance of composite materials. In addition, patent CN116285004 discloses a method of plating metal on the surface of carbon fibers by a chemical method to achieve electromagnetic shielding function, wherein the surface of the carbon fibers is copper-plated on the inner layer and nickel-cobalt-phosphorus-plated on the outer layer. The treatment of the carbon fiber surface by complex physical and chemical methods is very complicated, which greatly increases the preparation cost of the composite material and is not universal, and is difficult to be used in engineering applications in large quantities. Therefore, it is necessary to design a method that can realize the deposition of a large amount of functional nanoparticles on the surface of carbon fibers by a simple, efficient, economical and green method, for the construction of a structure / function integrated composite material. At the same time, the carbon fiber surface modification method should make the filler evenly distributed in the composite material, and can avoid the filtering effect of the fiber bundle on the filler during the preparation of the composite material.
[0004] The purpose of the present invention is to provide a carbon fiber surface modification method based on the principle of electrostatic layer-by-layer self-assembly, by which graphene oxide sheet structures and nanoparticles with opposite charges are electrostatically self-assembled on the carbon fiber surface, and the content of nanoparticles on the carbon fiber surface can also be regulated by the number of assemblies. Summary of the invention:
[0005] The purpose of the present invention is to provide a carbon fiber surface modification method based on the principle of layer-by-layer electrostatic self-assembly, by assembling graphene oxide sheet structures and nanoparticles with opposite charges on the surface of carbon fibers layer by layer, to provide an efficient preparation method for the construction of structural / functional integrated composite materials, and at the same time, the functional filler can have a high content on the fiber surface and be evenly distributed in the composite material, avoiding the filtering effect of the fiber bundle on the filler during the preparation of the composite material. The technical solution adopted by the present invention is as follows:
[0006] 1. A carbon fiber surface modification method based on the layer-by-layer electrostatic self-assembly principle, the main preparation method of which takes the following steps:
[0007] Step 1: Immerse the carbon fiber in an acetone solution to remove the sizing agent, and then immerse it in a cationic polyelectrolyte solution, wash it with water, and dry it to make the surface of the carbon fiber positively charged. In addition, ultrasonically disperse the single or multi-layer graphene oxide in a benign solvent, fully disperse it, and the surface charge of the graphene oxide sheet in the dispersion is negatively charged, and it is set aside.
[0008] Step 2: Treat the surface of the nanoparticles with a surface modifier and adjust the pH of the suspension of the modified nanoparticles so that the surface of the nanoparticles presents a positive charge in the aqueous solution.
[0009] Step 3: Immerse the positively charged carbon fiber treated with the cationic polyelectrolyte solution in step 1 in a negatively charged graphene oxide suspension, wash with water, dry, and then immerse in a positively charged functional nanoparticle suspension, wash with water, and dry to complete an assembly step. Repeat this step n times to achieve n-layer self-assembly modification of the carbon fiber surface.
[0010] The carbon fiber in step one is polyacrylonitrile-based carbon fiber, in the form of carbon fiber tow or carbon fiber fabric; the carbon fiber fabric includes one or more of carbon fiber unidirectional fabric, carbon fiber plain fabric, carbon fiber twill fabric, carbon fiber satin fabric and carbon fiber wrinkle-free fabric.
[0011] The cationic polyelectrolyte solution in step 1 is one or more of polyethyleneimine (PEI), polyacrylamine (PAM) and polyquaternary ammonium salt polymers, preferably polyethyleneimine (PEI), and the solution concentration is 1-5 mg / mL.
[0012] The surface modifier in step 2 is a hydroalcoholic solution of one or more of 3-aminopropyltriethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAPTMS), and 3-aminopropyldimethylethoxysilane (APDMES) after hydrolysis. Preferably, the reaction temperature of the surface modification is 60-100°C.
[0013] The nanoparticles in step 2 are one or more inorganic nanoparticles such as silicon oxide, zirconium oxide, tungsten trioxide, gadolinium boride, silicon carbide and boron carbide. The particle size of the nanoparticles is preferably 5nm-100nm, more preferably 10-80nm, and most preferably 10-50nm.
[0014] In the step 2, the pH of the aqueous solution of the surface-modified nanoparticles is adjusted, preferably to a pH < 7.
[0015] The concentration of the nanoparticle suspension in step 3 is selected to be 0.1-1 mg / ml, preferably 0.1-0.5 mg / ml, and more preferably 0.3-0.5 mg / ml.
[0016] The number of assembling times described in step three is 1-6 times, preferably 1-4 times.
[0017] More specifically, the present invention provides a carbon fiber surface modification method based on the layer-by-layer electrostatic self-assembly principle, and the specific preparation steps are as follows:
[0018] Step 1: Cut the purchased carbon fiber fabric and reflux it in acetone at 80℃±2℃ for 2-8h to remove the sizing agent and contaminants. Then immerse the desized carbon fiber in a cationic polyelectrolyte aqueous solution (1mg / mL) at 60℃ for 2 hours. The fiber fabric is washed twice with deionized water and dried at 80℃. The branched molecular structure of the PEI aqueous solution contains NH3 + 、NRH2 + and NR2H + The cationic polyelectrolyte (rich in amino groups) has a strong adsorption capacity and is physically adsorbed on the surface of the carbon fiber, giving the fiber surface a cationic charge.
[0019] Step 2: The amino coupling agent is hydrolyzed in the aqueous solution, making the aqueous solution alkaline and catalyzing the hydrolysis of the coupling agent. Dissolve 5-15 mL of the coupling agent in 30 mL of deionized water and treat it with ultrasound at room temperature for 10-30 minutes. After sufficient hydrolysis, let it stand for use. Then, disperse 1-5 g of nanoparticles in an ethanol solution and disperse them with ultrasound. Subsequently, add the hydrolyzed coupling agent solution and react in an oil bath at 70°C for 3 hours. Finally, filter the nanoparticles, wash them 3 times with deionized water, and dry them in an oven at 80°C to obtain modified nanoparticles.
[0020] Step 3: The carbon fiber treated in step 1 is immersed in a negatively charged graphene oxide (1 mg / mL) aqueous solution for 10 minutes, washed with deionized water and dried. At this time, the carbon fiber with negative charge polarity is immersed in a positively charged nanoparticle (1-5 mg / ml) solution for 10 minutes, then washed with deionized water and dried. During this period, the fabric is shaken to completely immerse in different solutions. This process is repeated n times to form a multilayer structure on the CF surface.
[0021] Preferably, the diameter of the nanoparticles is less than 100 nm, which is conducive to the dispersion of the nanoparticles in the fiber bundle.
[0022] The content of nanoparticles on the surface of the carbon fiber after the electrostatic self-assembly treatment is 0.5-10wt%.
[0023] The advantages of the carbon fiber surface modification method based on the layer-by-layer electrostatic self-assembly principle provided by the present invention are that the molding process is simple, efficient and highly applicable. (1) The graphene oxide sheet structure and the nanoparticles with opposite charges are assembled layer by layer on the carbon fiber surface, and the solution used is deionized water, which has the characteristics of simplicity, efficiency and environmental friendliness. (2) It has a wide range of applications and can be used for various types of carbon fibers and other types of fibers. The types of nanoparticles are not limited and the coverage is wide, which is easy to promote. (3) The content of nanoparticles on the fiber surface is controllable and can reach a high content. The content of nanoparticles on the carbon fiber surface can be adjusted by adjusting the solution concentration and the number of assembly times. In addition, the unique structure of the modified graphene oxide nano two-dimensional sheet can fully interact with the nanoparticles, and the nanoparticles on the carbon fiber surface can reach a high content. (4) The functional filler can give the composite material certain functional properties, such as thermal conductivity, electromagnetic shielding and radiation shielding. This method provides an efficient preparation method for the construction of functional-structural integrated composite materials. (5) In the preparation process of ordinary composite materials, the fiber bundle will filter the functional filler, causing the filler to be mainly distributed between the fiber bundles, thereby affecting the performance. This method can distribute the functional filler on the surface of the carbon fiber filaments, so that it is evenly distributed in the composite material. Description of the drawings:
[0024] Figure 1 : Schematic diagram of electrostatic layer-by-layer self-assembly
[0025] Figure 2 : Zeta potential of graphene oxide solution, modified nano-boron carbide (ZETA potential of GO solution (a) and ZETA potential of modified B4C in different pH solutions: PH = 7 (b), PH = 5 (c) and PH = 3 (d) Figure 2 (shown)
[0026] Figure 3: Microscopic scanning electron micrographs of the carbon fiber surface before and after assembly (microscopic morphology of unmodified fiber, assembled twice and assembled four times as shown in Figure 2) Figure 3 (shown)
[0027] Specific implementation cases:
[0028] Preparation Example Nano boron carbide treated with silane coupling agent KH550
[0029] T700 grade unidirectional carbon fiber fabric U-7200 (surface density 210g / m 2 ) After cutting, the carbon fiber was refluxed in acetone at 80°C for 8 hours to remove the sizing agent and contaminants. Then, the desized carbon fiber was immersed in a PEI aqueous solution (1 mg / mL) at 60°C for 2 hours, and the fiber fabric was washed twice with deionized water and dried at 80°C for use.
[0030] The surface of the nano-B4C was modified by using a coupling agent KH-550 containing an amino group. Since KH-550 is an amino coupling agent, the amino group is hydrolyzed in the aqueous solution to make the aqueous solution alkaline, thereby catalyzing the hydrolysis of the coupling agent. Therefore, it is not necessary to adjust the pH by acid or alkaline substances. First, 15 mL of KH550 was dissolved in 30 mL of deionized water and ultrasonically treated at room temperature for 30 minutes. After the coupling agent KH-550 was fully hydrolyzed, the suspension changed from milky white to transparent and was left to stand for use. Then, 5 g of nano-B4C was dispersed in 300 mL of ethanol solution and ultrasonically treated for 20 minutes. Subsequently, the freshly hydrolyzed KH550 solution was added and reacted in an oil bath at 70 ° C for 3 hours. Finally, the nano-B4C was filtered using an organic filter membrane (200 nm), washed with deionized water 3 times, and dried in an oven at 80 ° C to obtain modified B4C, and the pH was adjusted to 5. The zeta potential at this time was +21.7 mV.
[0031] Example Properties of self-assembled modified carbon fibers and composites prepared from them
[0032] Micro-debonding test interface performance: The carbon fiber tow is divided into single filaments and glued to the U-shaped mold to make the resin form fine resin droplets; the fiber single filaments with resin droplets are put into the oven for curing. After curing, the micro-debonding test equipment is used to test the interface bonding strength between the resin and the fiber.
[0033] Test method for the content of each component: The test includes the fiber, resin, boron carbide on the fiber surface and the B element content in the matrix. According to GB / T 3855-2005 standard, sulfuric acid / hydrogen peroxide solution is used to dissolve the resin matrix of the composite material and separate the fibers. Then, the solution containing nanoparticles is filtered through a 100nm filter membrane to separate the nanofiller and obtain the filler content.
[0034] Thermal neutron shielding performance test: The device uses He-3 detector, multi-channel pulse amplitude analyzer, amplifier and spectrum processing software to test its shielding performance.
[0035] Example 1 Electrostatic self-assembly of carbon fiber surface and preparation of its composite materials
[0036] The PEI-treated carbon fiber in the preparation example was immersed in a negatively charged graphene oxide (1 mg / mL) aqueous solution for 10 minutes, washed with deionized water and dried. At this time, the carbon fiber with negative charge polarity was immersed in a positively charged nanoparticle (1-5 mg / ml) solution for 10 minutes, then washed with deionized water and dried. The system with surface assembly treatment once was named CF_L1. The resin system for preparing the composite material is epoxy resin E51, and the curing agent is liquid modified aromatic amine. Wet impregnation, followed by hot pressing. The prepared laminate consists of 10 layers of fabric, and the curing process is: 60℃ / 1h, 100℃ / 1h (1MPa), 150℃ / 2h (1MPa), 180℃ / 2h (1MPa).
[0037] Example 2 Secondary electrostatic self-assembly of carbon fiber surface and preparation of its composite materials
[0038] Similar to the operating steps in Example 1, the PEI-treated carbon fiber in the preparation example was immersed in a negatively charged graphene oxide (1 mg / mL) aqueous solution for 10 minutes, washed and dried. The carbon fiber with negative charge polarity was immersed in a positively charged nanoparticle (1-5 mg / ml) solution for 10 minutes, then washed with deionized water and dried. The self-assembly operation of graphene oxide and nano-boron carbide was repeated 2 times, and the system with surface assembly treatment 2 times was named CF_L2. Then, the method of Example 1 was used for wet impregnation and hot pressing.
[0039] Example 3 Electrostatic self-assembly of carbon fiber surface four times and preparation of its composite materials
[0040] Similar to the operating steps in Example 1, the PEI-treated carbon fiber in the preparation example was immersed in a negatively charged graphene oxide (1 mg / mL) aqueous solution for 10 minutes, washed with water, and dried. The carbon fiber with negative charge polarity was immersed in a positively charged nanoparticle (1-5 mg / ml) solution for 10 minutes, then washed with deionized water and dried. The assembly operation of graphene oxide and nano-boron carbide was repeated 4 times, and the system with 4 surface assembly treatments was named CF_L4. Then, the method of Example 1 was used for wet impregnation and hot pressing.
[0041] Comparative Example 1 Preparation of untreated carbon fiber and its composite materials
[0042] The carbon fiber fabric without surface modification is prepared into a composite material by wet impregnation and hot pressing according to the method of Example 1. The prepared composite material system is called CF_0.
[0043] Application Example 1 Thermal neutron shielding performance test
[0044] The shielding ability of composite materials against thermal neutrons is calculated based on Lambert-Beer, as shown in formula (1):
[0045] I1=I0e -μt (1)
[0046] Where μ is the linear attenuation coefficient (cm -1 ) ; t is the sample thickness (cm); the net count when the sample is empty is I0; the net count when the shielding material is placed is I1. From this, the gamma ray transmittance of materials of different thicknesses can be obtained I1 / I0, and the linear attenuation coefficient μ can be calculated, in cm -1 The thermal neutron energy in this paper is <1eV.
[0047] The content of nano-boron carbide in all samples and its corresponding linear attenuation coefficient were characterized. The results are shown in Table 1. The B4C content on the carbon fiber surface gradually increased with the increase of the number of assembly times. The contents after assembling 2 and 4 times reached 4.3wt.% and 7.9wt.%, respectively. The thermal neutron shielding performance was improved by 136% and 242% respectively compared with the unmodified system.
[0048] Table 1 The content of carbon fiber surface self-assembly n times and the content of each component of the composite material prepared therefrom, as well as the thermal neutron linear attenuation absorption μ (cm -1 )
[0049]
[0050] Application Example 2 Micro-debonding test of its interface performance
[0051] The carbon fiber tow is divided into single filaments and glued to a U-shaped mold. The resin is absorbed by a needle and evenly dripped on the surface of the carbon fiber single filament to form fine resin droplets. The fiber single filament with the resin droplets is placed in an oven for curing. After curing, the interface bonding strength between the resin and the fiber is tested using a micro-debonding test device. Two metal blades are used to load the epoxy droplets at a speed of 0.06 mm / min, and the maximum load during the test is recorded. The interface bonding strength can be calculated using formula (2):
[0052]
[0053] Where F is the maximum load recorded, d f is the diameter of the carbon fiber to be accurately measured, l eis the embedded length. The diameter of the fiber used is 7 μm.
[0054]
[0055] From the above test results, it can be seen that the interface strength of the carbon fiber surface is enhanced after being assembled and modified by graphene oxide and nano-boron carbide. Figure 3 It can be seen that the carbon fiber surface is wrapped by nanoparticles after assembly modification, the interface bonding force between the resin matrix and the fiber is enhanced, and its interface strength is improved.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. The present invention provides a carbon fiber surface modification method based on the layer-by-layer self-assembly principle, which is mainly characterized by: Take the following steps: Step 1: Immerse the carbon fiber in an acetone solution at 80℃±2℃ and reflux for 2-8h to remove the sizing agent, then immerse it in a cationic polyelectrolyte solution, wash it with water, and dry it to make the surface of the carbon fiber positively charged. In addition, ultrasonically disperse a single layer or multilayer of graphene oxide in a benign solvent, and the surface charge of the graphene oxide sheet in the dispersion is negatively charged, and set aside. Step 2: Treat the surface of the nanoparticles with a surface modifier and adjust the pH of the suspension of the modified nanoparticles so that the surface of the nanoparticles presents a positive charge in the aqueous solution. Step 3: Immerse the positively charged carbon fiber treated with the cationic polyelectrolyte solution in step 1 in a negatively charged graphene oxide suspension, wash with water, dry, and then immerse in a positively charged functional nanoparticle suspension, wash with water, and dry to complete an assembly step. Repeat this step n times to achieve n-layer self-assembly modification of the carbon fiber surface.
2. The method according to claim 1, characterized in that The carbon fiber is polyacrylonitrile-based carbon fiber, and its form includes carbon fiber tow or carbon fiber fabric; the carbon fiber fabric includes one or more of carbon fiber unidirectional fabric, carbon fiber plain fabric, carbon fiber twill fabric, carbon fiber satin fabric and carbon fiber wrinkle-free fabric.
3. The method according to claim 1, characterized in that The cationic polyelectrolyte solution is one or more of polyethyleneimine (PEI), polyacrylamine (PAM) and polyquaternary ammonium salt polymers, and the preferred solution concentration is 1-5 mg / mL.
4. The method according to claim 1, characterized in that The surface modifier is a hydroalcoholic solution of one or more of 3-aminopropyltriethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAPTMS), and 3-aminopropyldimethylethoxysilane (APDMES) after hydrolysis, and the reaction temperature of the surface modification is 60-100°C.
5. The method according to claim 1, characterized in that The nanoparticles are one or more inorganic nanoparticles such as silicon oxide, zirconium oxide, tungsten trioxide, gadolinium boride, silicon carbide and boron carbide.
6. The method according to claim 5, characterized in that The particle size of the nanoparticles is preferably 5 nm-100 nm, more preferably 10-80 nm, and most preferably 10-50 nm.
7. The method according to claim 1, characterized in that The concentration of the nanoparticle suspension is selected to be 0.1-1 mg / ml, preferably 0.1-0.5 mg / ml, and more preferably 0.3-0.5 mg / ml.
8. The method according to claim 1, characterized in that The pH of the surface-modified aqueous solution is adjusted to be acidic (pH < 7).
9. The method according to claim 1, characterized in that The number of assembling is 1-6 times, preferably 1-4 times.
10. The method according to claim 1, characterized in that The content of nanoparticles on the surface of carbon fiber after electrostatic self-assembly treatment is 0.5-10wt%.